PERSEPSI MASYARAKAT TENTANG PERNIKAHAN TANPA TATA CARA ADAT BATAK DI GEREJA MAWAR SARON JALAN HARAPAN JAYA KECAMATAN TENAYA RAYA KOTA PEKANBARU - Mia Yuliati Panjaitan; Hambali Hambali; Haryono Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract:The problem of this research is motivated by the existence of conflicts or tensions between customs and the Bible related to the procedures for traditional Batak marriages. This study aims to determine the public's perception of marriage without Batak tribal procedures, and the consequences if marriage without Batak traditional procedures in the Pentecostal Church. This research method is descriptive method, where this research is a qualitative research. The research location was set at the Pentecostal Church on Jalan Harapan Jaya, Tenayan Raya District, Pekanbaru. The informants of this study were 5 people. The data collection technique of this research is interviews, and is supported by observation and documentation. The data analysis of this research used qualitative analysis in the form of data reduction, power display, and verification. The results of this study indicate that the community's perception of marriage without Batak tribal procedures is known from the presence of couples who marry without using customs caused by economic factors and church teaching factors. There are also couples who get married without using the Batak tribe's customs, who think that without being attended to is also not a problem. The result of marriage without Batak customary procedures in the Pentecostal Church is not being able to participate in traditional activities in the form of giving or receiving ulos and jambars, rarely participating in clan associations (punguan) so as to create barriers to friendship with other clans, so that it becomes talk in traditional activities.Key Words: Perception,Marriage Without Batak Traditional Procedures